2021
DOI: 10.4236/ajac.2021.125010
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherm, Kinetic and Thermodynamic Modelling of <i>Bacillus subtilis</i> ATCC13952 Mediated Adsorption of Arsenic in Groundwaters of Selected Gold Mining Communities in the Wassa West Municipality of the Western Region of Ghana

Abstract: This study investigated Bacillus subtilis ATCC13952 as an adsorbent for arsenic in groundwater. Batch experiments were used to determine the effect of contact time, adsorbent dose, arsenic (III) concentration, pH, and temperature on the process. The percentage of arsenic (III) removed was high at a contact time of four days, 3.0 mL of Bacillus subtilis ATCC13952, pH 8 and temperature of 35˚C. The kinetics of the process showed the Elovich kinetics model as the best fit for the process. This indicates that arse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…Moreover, positive values of enthalpy change (∆H • ) and entropy change (∆S • ) demonstrated that the process was endothermic and favorable in nature. The results of our study are in agreement with Asare et al [57].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, positive values of enthalpy change (∆H • ) and entropy change (∆S • ) demonstrated that the process was endothermic and favorable in nature. The results of our study are in agreement with Asare et al [57].…”
Section: Discussionsupporting
confidence: 94%
“…This model provides a similar conclusion to the Langmuir model; however, the Redlich-Peterson model accommodates the determination of surface-binding vibrations of an adsorbed species [60]. The Redlich-Peterson serves as a bridge determined as a compromise for Langmuir and Freundlich adsorption processes to clarify the preeminence of either heterogeneous or homogenous adsorption in a system [61]. From the results provided in Figure 5e, the Redlich-Peterson constant (A R ) of 4.94 × 10 11 L g −1 and β values of 1.40 mg L −1 were determined for the adsorption of E. coli, suggesting that the TM@ZnO/TMC NC hydrogel as biosorbent has an affinity for E. coli in aqueous systems [60].…”
Section: Studies Of Adsorption Isothermmentioning
confidence: 92%